2020
DOI: 10.1111/caim.12384
|View full text |Cite
|
Sign up to set email alerts
|

Struggles as triggers in a design‐thinking journey

Abstract: The scholarly and practitioner literatures have both described the potential benefits of Design Thinking (DT) to develop innovations. Innovation processes are widely characterized by continuous competing demands, which generate tensions. The paper analyzes a DT innovation journey, focusing on the struggles and triggers of participants as they work through conflicting demands. Following a qualitative inductive research design, the study reports on the experience of a group of management students exposed intenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Paper 7: Struggles as triggers in a design thinking journey Whereas the benefits of design thinking as an approach to developing innovations are widely recognized, it is also important to acknowledge the tensions the approach creates-particularly to design thinking novices. To shed light on these tensions, Coco, Calcagno, and Lusiani (2020) conducted a qualitative study focusing on the struggles that management students face during a design thinking innovation journey. Employing inductive reasoning, they organize the participants' experiences, opinions, feelings and cognition into three main categories of struggles and triggers, identified as destabilizing, non-deciding and abstracting.…”
Section: 7mentioning
confidence: 99%
“…Paper 7: Struggles as triggers in a design thinking journey Whereas the benefits of design thinking as an approach to developing innovations are widely recognized, it is also important to acknowledge the tensions the approach creates-particularly to design thinking novices. To shed light on these tensions, Coco, Calcagno, and Lusiani (2020) conducted a qualitative study focusing on the struggles that management students face during a design thinking innovation journey. Employing inductive reasoning, they organize the participants' experiences, opinions, feelings and cognition into three main categories of struggles and triggers, identified as destabilizing, non-deciding and abstracting.…”
Section: 7mentioning
confidence: 99%
“…Carlgren, Elmquist, and Rauth (2016) identified seven types of DT implementation challenges: DT often does not fit with existing processes and structures, resulting ideas and concepts are challenging to implement, the value of DT is difficult to prove, DT principles/mindsets clash with organizational cultures, existing power dynamics are threatened, skills are hard to acquire and communication styles differ. In a recent article, Coco et al (2020) identified three main struggles and tensions for new adopters of the DT process: destabilization (conflict between demand for control and disruption), indecision (conflict between deductively solving problems and inductively generating ideas) and abstraction (conflicting demands for facts vs. new ideas). They argued that these struggles and tensions are not only an inherent part of every DT project but a desirable part of the journey.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In a recent article, Coco et al (2020) identified three main struggles and tensions for new adopters of the DT process: destabilization (conflict between demand for control and disruption), indecision (conflict between deductively solving problems and inductively generating ideas) and abstraction (conflicting demands for facts vs. new ideas).…”
Section: Dt Facilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 lists all 17 papers and their key insights. Coco et al (2020) Novices in design thinking such as marketing and business students face three struggles during a design thinking innovation journey: destabilizing, non-deciding, and abstracting Baumgarth and Bahati Wieker (2020) Urban art, such as street art and graffiti, positively affects consumers' product evaluation Nagel and Schumann (2020) Consumers' perceptions of the innovative aesthetic value buffer the effect of product-related hedonic experience on attitudes toward the product Carvajal Pérez et al (2020) Creative heritage-a type of cognitive resource-can help marketing and design teams in luxury organizations to address destructive and creative tensions and overcome the trade-off between product innovativeness and brand consistency Artusi and Bellini (2020) To embody new meaning in a new service, the service concept must be simple and focused on one concrete element in the customer journey, the so-called "Moment of Meaning"…”
Section: Marketing and Designmentioning
confidence: 99%